Is Administration Leaner in Charter Schools? Resource Allocation in Charter and Traditional Public Schools - Arsen, David D.; Ni, Yongmei (Education Policy Analysis Archives, 2012)
There is widespread concern that administration consumes too much of the educational dollar in traditional public schools, diverting needed resources from classroom instruction and hampering efforts to improve student outcomes.  By contrast, charter schools are predicted to have leaner administration and allocate resources more intensively to instruction. This study analyzes resource allocation in charter and district schools in Michigan, where charter and tradition public schools receive approximately the same operational funding.  Controlling for factors that could affect resource allocation patterns between school types, we find that charter schools on average spend $774 more per pupil per year on administration and $1141 less on instruction than traditional public schools.